Microsatellite Variation of African Elephants Loxodonta africana Blumenbach 1797 in a Savannah Protected Area of South Sudan - Thomas Francis Lado; Wani Felix Jibi; Pasquale Tiberio Moilinga (Ecology and Evolution)
ABSTRACT Anthropogenic activities such as poaching and habitat loss lead to a drop in population size, range overlap and hybridisation. The decline in population size results in reduced genetic diversity, an increase in homozygosity and inbreeding. Here, we genotyped 16 polymorphic microsatellite loci on 80 elephant dung samples to determine genetic diversity, genetic bottleneck, genetic relatedness and inbreeding in the savannah elephant in Nimule National Park, which experienced an 80% fall in population size. Results revealed that the elephant population in the park comprised 26 savannah elephants. The study also found genetic variation, average number of observed alleles Ao, observed heterozygosity Ho and expected heterozygosity He to be 5.31 ± 2.62, 0.61 ± 0.22 and 0.56 ± 0.21, respectively, but with no difference between observed Ho and expected He heterozygosity. There was no evidence that the elephant population in the park went through a recent genetic bottleneck (p = 0.94167; and normal L‐shaped distribution); however, evidence for a historical bottleneck was detected (M ratio = 0.44 ± 0.22). Mean pairwise relatedness was generally low (ML‐r = 0.09 ± 0.22) with a high proportion of unrelated individuals (U = 85.8%), and there was no indication of inbreeding (FIS = −0.08, p > 0.05). We conclude that the observed decline in the population size is not an artefact of using different methods, as shown by the historical bottleneck. Despite the observed reduction in census size, there is an exchange of individuals with the neighbouring savannah elephant population.